One-Pot Synthesis of Diaryl Sulfonamides using an Iron- and Copper-Catalyzed Aryl C–H Amidation Process - Waddell, Lachlan J. N.; Henry, Martyn C.; Mostafa, Mohamed A. B.; Sutherland, Andrew (Synthesis, 2022)
A one-pot, two-stage synthesis of diaryl sulfonamides using sequential iron and copper catalysis is developed. Regioselective para-iodination of activated arenes by the super Lewis acid, iron triflimide and N-iodosuccinimide (NIS), is followed by a copper(I)-catalyzed N-arylation reaction. The process is found to be applicable for the coupling of a range of anisoles, anilines and acetanilides with primary sulfonamides and is used for the one-pot synthesis of biologically important compounds.
Keywords: sulfonamides; iron catalysis; copper catalysis; aryl substitution